Evidence of high body temperature during men's stage-race cycling in temperate environmental conditions - Ross, M. L. R.; Stephens, B.; Abbiss, C. R.; Martin, D.T.; Laursen, P. B.; Burke, L. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Hyperthermia, hypohydration and carbohydrate (CHO) depletion have been recognized as likely factors influencing fatigue during prolonged endurance cycling. However, there is currently limited field-based research examining the occurrence of hyperthermia and real-life fluid and fuel practices of athletes, especially during exercise in temperate conditions. Therefore, the aims of this study were to observe the thermoregulatory stress, fluid balance and voluntary CHO intake of highly competitive road cyclists during a multiday multiple-stage race in temperate conditions. Methods: Ten internationally competitive male cyclists competed in two cycling stage-races (2009 Tour of Gippsland; n=5, and 2010 Tour of Geelong; n=5) in temperate conditions (15.8±1.4°C; 54±12%r.h., and 13.2±2.1°C; 80±8%r.h, respectively). Body mass (BM) was recorded immediately before and after each stage. Peak gastrointestinal temperature (TGI) was recorded throughout each stage. Cyclists recalled the types and volumes of fluid and food consumed throughout each stage. Results: Overall general classification of cyclists ranged from 1st to 97th placing with 5 stage wins in the Tour of Gippsland, and 3 stage wins in the Tour of Geelong. The mean change in BM during stages of the Tour of Gippsland, was - 1.3±0.2%, with only 5 out of 43 occasions where subjects were observed to exceed a deficit of >2% BM. There was a very large negative correlation (r=-0.8) between fluid deficit and stage finish time. Mean fluid consumption was 771-1658 ml (0.41-0.64 L/h) during road, and 210-432 ml (0.24-0.27 L/h) during criterium stages. There was a large correlation (r=0.95, and r=0.88) between fluid intake and stage distance observed in both tours. Mean CHO consumption was 85-200g (44-77 g/h or 1.18-2.84 g/kg BM) during road, and 24-37 g (28- 29 g/h or 0.34-0.52 g/kg BM) during criterium stages. 67% and 73% of peak TGI observed during the Tour of Gippsland (mean peak TGI=38.9±0.7°C) and the Tour of Geelong (39.3±0.4°C) were >39°C. Discussion: This study captured novel and insightful data on the thermoregulatory stress, fluid balance and voluntary CHO intake of highly competitive cyclists during a multiday multiple-stage road race preformed in temperate conditions. In the present study we consistently observed TGI associated with hyperthermic-induced fatigue. Further, cyclists in this study experienced only mild fluid deficit and matched recommended rates of CHO consumption during exercise, however interpretation of fluid balance on cycling performance is made difficult by race tactics. Further research is required to determine the impact of elevated body temperature on cycling performance in temperature conditions.